Implementation of Revised Simplified Geneva Score in Triage Nurse Evaluation for Patients With Suspected Pulmonary Embolism: A Retrospective Chart Review - Nicola Osti; Alberto Maino; Giulia Moreschini; Cristina Marinconz; Nicola Susca; Cristina Contu; Vito Racanelli; Anna Brugnolli (Emergency Medicine International)
Conclusions: The current 5LT was unable to differently prioritize patients with or without PE, and it seems unlikely that implementation of SRGS in the triage nurse evaluation will significantly improve the prioritization of patients with suspected PE for medical evaluation. Nonetheless, application of SRGS in triage evaluation may improve the appropriateness of the subsequent clinical pathway for PE diagnosis and risk stratification.